2018
DOI: 10.1161/jaha.118.009592
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of Left Ventricular Size and Sex on Outcome of Cardiac Resynchronization Therapy Among Patients With a Narrow QRS Duration in the EchoCRT Trial

Abstract: BackgroundLonger QRS duration (QRSd) improves, but increased left ventricular (LV) end‐diastolic volume (LVEDV) reduces, efficacy of cardiac resynchronization therapy (CRT). QRSd/LVEDV ratios differ between sexes. We hypothesized that in the EchoCRT (Echocardiography Guided Cardiac Resynchronization Therapy) trial enrolling patients with heart failure with QRSd <130 ms, those with larger LVEDV would deteriorate but those with the highest QRSd/LVEDV would improve with CRT.Methods and ResultsPrimary outcome in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…This is consistent with studies on CRT with narrow QRSd, in which unlike males, females with narrow QRSd did not have increased mortality rates with CRT ( 5 ). A recent study also found that a smaller LV size was associated with improved CRT response in patients with QRSd <130 ms ( 21 ), supporting lower narrow QRSd threshold for females who generally have smaller LV sizes.…”
Section: Discussionmentioning
confidence: 85%
“…This is consistent with studies on CRT with narrow QRSd, in which unlike males, females with narrow QRSd did not have increased mortality rates with CRT ( 5 ). A recent study also found that a smaller LV size was associated with improved CRT response in patients with QRSd <130 ms ( 21 ), supporting lower narrow QRSd threshold for females who generally have smaller LV sizes.…”
Section: Discussionmentioning
confidence: 85%
“…The degree of LV dilatation has been linked to a range of efficacy experienced with pharmacological, device or surgical treatments. 23,24 It is further unmasked herein as a determinant of stem cell-promoted cardiac repair. in vivo functional and structural restoration was reinforced by molecular validation at proteome level.…”
Section: Discussionmentioning
confidence: 99%
“…ey describe the efficacy of CRT, as well as the existence of dyssynchrony in patients with a narrow QRS complex [14,[20][21][22]. Varma et al reported efficacy in patients with a narrow QRS complex <130 ms from the EchoCRT trial and concluded that CRT may be beneficial in patients with HF with a narrow QRS and smaller ventricles [23]. Indeed, in clinical practice, we often see patients who respond well to CRT despite the fact that their QRS is relatively narrow at <130 ms [15,24].…”
Section: Crt In Patients With a Narrow Qrs Complexmentioning
confidence: 99%